Warfarin Induced Abnormal Uterine Bleeding: A Case Report - Abraham, Emi Rose; Salimath, Geetanjali (Journal of Pharmacy Practice and Community Medicine)
Background: The objective of this clinical case report is to highlight the importance of early identification of patients who are at a higher risk of developing bleeding complications after receiving Warfarin. Case Presentation: A 40 year old female patient visited the tertiary care hospital’s Gynecology OPD on 1st April 2021 with the complaints of heavy menstrual cycle for last eight months along with increased frequency of cycles. She had undergone Tubectomy 18years back during which she was diagnosed with Cardiac disease. Two years back she was diagnosed with Hypothyroidism and is on medication. One year back she had complaints of bilateral upper and lower limb weakness for which she visited a local hospital and found abnormalities in her ECG report. She underwent Aortic Valve Replacement surgery in July 2020 and was given Warfarin 5mg and a Beta- Blocker. After a month of surgery the patient noticed increased menstrual flow along with increased frequency of menses, lasting for 10-12 days. The patient was admitted and underwent hysterectomy. Post-surgery Warfarin dose was increased to 7.5mg once daily. Discussion: The risk of bleeding while taking Warfarin increases with certain factors like: – advanced age, drug-drug interactions, genetic polymorphism and gender- usually females require a lower dose of anticoagulants. In this case two possible drug-drug interactions were identified. As she is also a known case of hypothyroidism her risk for developing bleeding complications increases further. Conclusion: The case highlights the need for anticoagulation clinics in the hospitals, use of software’s in monitoring and dosage adjustments in such patients, use of risk stratification tools to identify high risk patients and also the need for self-monitoring by the patients.
Keywords: Anticoagulants; Warfarin; Drug Interactions; Hypothyroidism; Menstrual cycle